Lithium recovery from secondary sources: A review in battery recycling with emphasis on chemical precipitation - Ramirez Velazquez, Lorena E.; Muhr, Hervé (Comptes Rendus. Chimie, 2025)
The growing demand and rising prices of lithium have been driven by the expanding market of electrical vehicles and electronic devices. Therefore, the recovery of lithium from Li-ion batteries has gained enormous relevance. This document provides an overview of lithium’s role in the battery industry in the ongoing energy transition. It also explores the various processes used over the years to extract valuable metals from spent lithium-ion Batteries and provides an up-to-date review of the current recycling methodologies applied to batteries. This work particularly emphasizes the hydrometallurgical process involving the chemical precipitation of lithium carbonate. Indeed it is the most sought-after form in the lithium value chain. This route had demonstrated good recovery yields as well as high purity levels. This method stands out from other recycling methods since it is environmentally friendly, consumes little energy, and does not require a large number of chemical reagents. This work encourages further exploration and refinement of hydrometallurgical practices to make recycled lithium a viable source for the battery supply chain.